Single-cell transcriptional profiling reveals developmental dynamics of longissimus dorsi muscle in adult and Juvenile bactrian camels - De, Baojun; Liu, Yiyi; Li, Lu; Meng, Fanhua; Liu, Yuwen; Jia, Ting; Chen, Yuting; Liu, Chunxia; Wang, Shenyuan; Li, Tao; Xiao, Hongmei; Wan, Fang; et al. (Frontiers in Physiology, 2025)
IntroductionThe longissimus dorsi muscle of Bactrian camels holds significant biological and economic value. However, the cellular heterogeneity, lineage differentiation patterns, and intercellular communication mechanisms underlying its skeletal muscle development remain unclear, which has hampered the advancement of precise regulation of camel meat quality traits and genetic improvement of the breed. Accordingly, there is an urgent need to elucidate the developmental regulatory mechanisms of this muscle tissue at the single-cell level.MethodsIn this study, longissimus dorsi muscle tissues from 4-day-old (juvenile) and 5-year-old (adult) Bactrian camels were selected as research subjects. Integrated single-nucleus RNA sequencing (snRNA-seq) was employed to obtain gene expression data, which was coupled with Monocle2 pseudotime analysis, CellChat-based intercellular communication dissection, Gene Ontology (GO) enrichment analysis, and C2C12 cell functional validation experiments to conduct a systematic investigation into the cellular characteristics and developmental mechanisms of the Bactrian camel longissimus dorsi muscle.ResultsA total of 14 cell clusters were identified, and the cellular composition of muscle tissues differed significantly between age groups—juvenile camel muscles were enriched with proliferative cell populations such as muscle satellite cells (MuSCs) and fibroblast-like progenitor cells (FAPs), while adult camel muscles were dominated by mature type IIX/IIA fast-twitch muscle fibers. Further analysis revealed that MuSCs exhibited bidirectional differentiation potential towards type I slow-twitch muscle fibers and type IIA/IIX fast-twitch muscle fibers, and the PCDH7 gene was found to promote myogenic differentiation. Additionally, four FAP subpopulations were characterized, among which the MME+ FAP subpopulation was closely associated with intramyocellular fat (IMF) deposition.DiscussionThis study, for the first time, constructed a single-cell atlas and intercellular communication network of the Bactrian camel longissimus dorsi muscle, uncovered the key regulatory mechanisms governing its skeletal muscle development, and identified functionally important regulatory targets such as PCDH7. These findings not only provide a theoretical basis for the precise improvement of camel meat quality but also laid the groundwork for in-depth investigations into the adaptive evolutionary mechanisms of camel skeletal muscle.